Geological history reviews and geological aspects of shallow volcanic soil related to earthquake-induced landslide in Kumamoto 2016 - T.T.T. Tran; H. Hazarika (Lowland Technology International, 2018)
This paper aims to investigate geological conditions of shallow volcanic soil at the landslides effected area in Aso Volcanological Laboratory, Minamiaso Village, Kumamoto Prefecture, Japan that is caused by Kumamoto earthquake during April 14 to April 16, 2016. Earthquake-induced landslides occurred in Aso Volcanological Laboratory are characterized by long flows covering large areas with inclination of about 11o. The slope was composed dominantly of volcanic ash layers those have been altered to soil layers with different colours and engineering properties. Geological aspect of shallow soil profile includes volcanic lava and ash-fall tephra those are younger than 31ka lies on the old Takanoobane volcanic deposit (51ka). The Kusasenrigahama pumice-derived soil has been considered as the main source of the landslide.